Anomalous right coronary artery origin from pulmonary artery associated with aortic stenosis, mitral regurgitation, and Vieussens' arterial ring: a very rare association and case. Issue 2 (February 2021) - Musuraca, Gerardo; Imperadore, Ferdinando; Terraneo, Clotilde; Agostoni, Pierfrancesco; Tezza, Michela; Fornasa, Francesca; Albiero, Remo
Abstract: We report a very rare case of anomalous origin of the right coronary artery from the pulmonary artery associated with severe aortic stenosis, severe mitral regurgitation, and Vieussens' arterial ring (VAR). Diagnosis was made accidentally during preoperative coronary angiography and confirmed by multidetector computed tomography. Surgery was performed with aortic valve replacement, mitral valve annuloplasty, right coronary artery reimplantation into the ascending aorta, and VAR resection. <Learning objectives: The association of severe aortic stenosis, severe mitral regurgitation, anomalous origin of the right coronary artery from the pulmonary artery (ARCAPA), and Vieussens' arterial ring (VAR) is extremely rare. Multidetector computed tomography can confirm the diagnosis of ARCAPA and VAR, exclude a bicuspid aortic valve, and provide comprehensive preoperative anatomic information. Surgical correction with aortic valve replacement, mitral valve annuloplasty, right coronary artery reimplantation into the ascending aorta, and VAR resection should be preferred in patients with deemed acceptable surgical risk. A conservative treatment limited to transcatheter aortic-valve replacement might be considered in patients with a very high surgical risk.>